2022
DOI: 10.15586/aei.v50i4.623
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane ameliorates LPS-induced inflammatory injury of HK-2 cells through Sirtuin1/NF-κB pathway

Abstract: The anesthetic sevoflurane (SEV) has been shown to protect against organ’s injury during sepsis. The present study intended to uncover the protective effects of SEV on sepsis-induced acute kidney injury (SI-AKI) and its possible mechanism. Human renal tubular epithelial cell HK-2 was treated with 10 μg/mL lipopolysaccharide (LPS) to construct SI-AKI cell model. LPS-induced HK-2 cells were pretreated with SEV in the absence or presence of EX527, an inhibitor of Sirtuin 1 (SIRT1), after which were the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The reported incidence of AKI in septic patients ranges from 22% to 53%. Previous studies have shown that damage to RTEC is a main underlying cause of AKI 2 . KDM2B is involved in numerous pathological processes, for instance, cell senescence and tumor development 5 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reported incidence of AKI in septic patients ranges from 22% to 53%. Previous studies have shown that damage to RTEC is a main underlying cause of AKI 2 . KDM2B is involved in numerous pathological processes, for instance, cell senescence and tumor development 5 .…”
Section: Discussionmentioning
confidence: 99%
“…HK‐2 cells which are epithelial cell line from normal adult human kidney were maintained in DMEM added with 10% FBS in a 37°C incubator supplied with 5% CO 2 . For the AKI model establishment, the HK‐2 cells were treated with 10 μg/mL LPS for 24 h to induce sepsis‐associated AKI 2,9 . The LPS‐induced HK‐2 cells were treated with 1 μM SR11302 as an AP‐1 inhibitor or JSH‐23 as an NF‐κB inhibitor, 10 48 h later, the supernatant was used for cytokines analysis and the cells were collected for western blots analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations